Effectiveness Of Rapid Diagnostic Test (RDT) Versus Microscopic Examination Versus Clinical Diagnosis In Diagnosing Malaria Patients With Plasmodium Falciparum And Plasmodium Vivax In Endemic Areas: A Literature Review - Nathalia Maria Ferdinand (Cendana Medical Journal, 2026)
Background: Based on the malaria eradication strategy of the World Health Organization (WHO), a rapid diagnosis of malaria in peripheral areas is needed so that effective treatment can be immediately given to reduce morbidity and mortality. Purpose: To compare the effectiveness of the Rapid Diagnostic Test (RDT), microscopic examination andclinical diagnosis in establishing malaria cases caused by Plasmodium falciparum and Plasmodium vivax in endemic areas. Methods: The method of searching for article datasources was carried out through the Google Scholarand PubMed (2015-2020) databases to retrieverelevant articles published in English and Indonesian.Key terms and phrases related to patients with Plasmodium falciparum malaria and Plasmodium vivax malaria in endemic areas, the effectiveness of the Rapid Diagnostic Test (RDT), microscopic examination, clinical diagnosis of malaria were used in the search for the subject. Results: Based on the results of a literature review from 29 journals consisting of the characteristics of theeffectiveness of examinations in patients withPlasmodium falciparum and Plasmodium vivax malaria in endemic areas, 29 journals used clinical diagnosis, on conventional diagnosis, 20 journals used the Rapid Diagnostic Test (RDT) method, 2 journals used microscopic examination and 7 journals using the combined method of the Rapid Diagnostic Test (RDT) and microscopic examination. By comparing the three types of examination methods, the results show that the Rapid Diagnostic Test (RDT) method is compared to microscopic examination and clinical diagnosis, so the Rapid Diagnostic Test (RDT) method is more effective when used in endemic areas. Conclusion: Based on a literature review of 29 research journals, it can be concluded that conventional diagnosis using the Rapid Diagnostic Test (RDT) method is proven to be more effective and fast in diagnosing malaria so that it can be used as analternative diagnostic method in patients withPlasmodium falciparum and Plasmodium vivax malaria, especially in endemic areas.